(untitled) (Research, Society and Development, 2022)
This study aims to investigate congruences between multiculturalism, inclusion and school Physical Education in the literature about the multicultural methodology in the scope of Physical Education, as an inclusive tool in the appreciation of cultural diversity and how it can contribute to the formation of a critical individual and socialized, based on the respect and dignity of the other. The methodological procedure used for this article was the narrative review. The article presents a brief history of physical education and the contributions of multiculturalism in an inclusive way, based on the idea that culture is a subsidy that nourishes the entire educational process and that plays an extremely important role in child development and in the teaching-learning process of the individual. Multicultural learning in physical education promotes an integral view of the body and the world, as it is not possible to isolate such knowledge from the context in which it is inserted. Valuing cultural diversity, seeking to expand historical, political and social knowledge through studies, recognition and experiences of cultures, contributing to the formation of the critical and socialized individual.